The Relationship between Mental Processes and Japan’s Unique Communication Style of Aisou - Rin Ito; Alexander Navarro; Jiro Takai (Intercultural Communication Studies, 1970)
The Relationship between Mental Processes and Japan’s Unique Communication Style of Aisou